2014
DOI: 10.1111/joa.12221
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical landmarks for the localization of the greater palatine foramen – a study of 1200 head CTs, 150 dry skulls, systematic review of literature and meta‐analysis

Abstract: Accurate knowledge of greater palatine foramen (GPF) anatomy is necessary when performing a variety of anaesthesiological, dental or surgical procedures. The first aim of this study was to localize the GPF in relation to multiple anatomical landmarks. The second aim was to perform a systematic review of literature, and to conduct a meta-analysis on the subject of GPF position to aid clinicians in their practice. One-hundred and fifty dry, adult, human skulls and 1200 archived head computed tomography scans wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 33 publications
4
35
2
1
Order By: Relevance
“…Previous studies reported a mean GPF-MMS distance of between 14.3 and 16.7 mm, which is comparable to the present study (13.8 ± 1.5 mm) ( Table 3). The mean distance between the two GPF in the present study was 27.6 mm, less than that reported by Urbano et al (2010) and Tomaszewska et al (2014) (Table 3). The pterygoid hamulus is palpable in the oral cavity and is therefore a suitable anatomical landmark from which to determine the location of the GPF.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous studies reported a mean GPF-MMS distance of between 14.3 and 16.7 mm, which is comparable to the present study (13.8 ± 1.5 mm) ( Table 3). The mean distance between the two GPF in the present study was 27.6 mm, less than that reported by Urbano et al (2010) and Tomaszewska et al (2014) (Table 3). The pterygoid hamulus is palpable in the oral cavity and is therefore a suitable anatomical landmark from which to determine the location of the GPF.…”
Section: Discussioncontrasting
confidence: 79%
“…El conocimiento específico y detallado de la conformación, ubicación, dirección, longitud, relaciones, contenido y diferencias etarias, étnicas y sexuales, permite abordar con éxito el FPM y el CPM, para procedimientos quirúrgicos odontológicos extensos o cuando otras técnicas anestésicas no puedan ser utilizadas por procesos infecciosos y/o inflamatorios en el sitio de punción, permitiendo realizar un correcto bloqueo anestésico local y troncular al nervio maxilar, ramo del nervio trigémino (Carrea;Alvarado et al;Malamed & Trieger, 1983;Malamed, 2006;Howard-Swirzinski et al, 2010;Lopes et al, 2011;Nimigean et al, 2013;Sheikhi et al, 2013;Ilayperuma et al, 2014;Tomaszewska et al, 2014;Rapado-González et al, 2015).…”
Section: Introductionunclassified
“…Tomaszewska et al . (), used a CT scan to determine anatomical landmarks for localisation of the greater palatine foramen in man. CT scans have been used to compare two different techniques for maxillary nerve blocks in horses and yielded very useful information on anatomical landmarks for these techniques (Staszyk et al .…”
Section: Advanced Imaging Guided Proceduresmentioning
confidence: 99%